Assessment of Physical activities among University Students during Covid-19 Pandemic - Autif Hussain Mangi; Fahim Ullah Khan; Laiq Zaman (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: The COVID-19 pandemic has affected the physical activity of people including university students. This study aimed to assess the physical activity of university students of Hyderabad and its adjoining areas during the peak time of the COVID-19 pandemic.METHODOLOGY: This cross-sectional study was conducted during the peak period of COVID-19 among 232 university students belonging to the University of Sindh who came from Hyderabad and its adjoining areas. The samples were collected via a simple random sampling method. The physical activity of male and female university students was compared and calculated by using SPSS software version 21 and MS Office 365. The significance level among groups was determined by applying a Chi-square test whereas the pre and post-responses were calculated by applying McNemar’s test. The  P-Value of < 0.05 was set as statistically significant.RESULTS: About 68.96% of females and 51.72% of male university students did not go for walking whereas 91.38% of females and 65.52% of males did not even prefer jogging activity. The results from McNemar’s Test Statistics about pre- and post-COVID-19 physical activity suggested that the walkers and non-walkers’ group had a significant change (x2=60.016, p<0.001), and the jogging and non-jogging group had also a significant difference (x2=113.009, p<0.001). The weight of university students before and after COVID-19 was significantly different (x2=30.414, p<0.05).CONCLUSION: The university students performed less than usual physical activity and mostly preferred a sedentary lifestyle during the period of the COVID-19 pandemic